Distinguishing selection pressures in an evolving communication system: Evidence from color-naming in “cross signing” - Byun, Kang-Suk; Roberts, Seán G.; de Vos, Connie; Zeshan, Ulrike; Levinson, Stephen C. (Frontiers in Communication, 2022)
Cross-signing – the emergence of an interlanguage between users of different sign-languages – offers a rare chance to examine the evolution of a natural communication system in real time. Here using an annotated video corpus of 340 minutes, we focus on the evolution of shared colour terms over the initial weeks of first encounters and examine the role of different selectional pressures – of frequency, content, conformity and interactional context. We show that attentional factors in interaction play a crucial role.